Universitas Ahmad Dahlan academic visit to UiTM Perak Branch / Hazliza Haron - Haron, Hazliza (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2020)
The Department of Business Management had welcomed the del-egates of Universitas Ahmad Dahlan (UAD) Yogyakarta to UiTM Perak Branch Seri Iskandar Campus and Bandaraya Ipoh Campus from 3 to 7 Oct 2019. A total of 25 students of Master in Manage-ment and 2 lecturers from UAD came for the academic visit. One of the activities was a fruitful sharing session between UiTM Perak Branch and UAD that took place in both Seri Iskandar and Bandaraya Ipoh Campuses. The itinerary for their visit included a sharing session by lecturers from the Department of Business Man-agement to the delegates that took place at Ibn Firnas Room, FSPU. Assoc. Prof Dr Nor Khasimah presented a topic on digital marketing whereas Dr Mohd Afandi Abu Bakar shared his knowledge on cur-rent issues affecting Malaysian economies.